Anti-Respiratory Syncytial Virus Activity of Plantago asiatica and Clerodendrum trichotomum Extracts In Vitro and In Vivo - Chathuranga, Kiramage (Viruses, 2019)
The herbs Plantago asiatica and Clerodendrum trichotomum have been commonly used for centuries in indigenous and folk medicine in tropical and subtropical regions of the world. In this study, we show that extracts from these herbs have antiviral effects against the respiratory syncytial virus (RSV) in vitro cell cultures and an in vivo mouse model. Treatment of HEp2 cells and A549 cells with a non-cytotoxic concentration of Plantago asiatica or Clerodendrum trichotomum extract significantly reduced RSV replication, RSV-induced cell death, RSV gene transcription, RSV protein synthesis, and also blocked syncytia formation. Interestingly, oral inoculation with each herb extract significantly improved viral clearance in the lungs of BALB/c mice. Based on reported information and a high-performance liquid chromatography (HPLC) analysis, the phenolic glycoside acteoside was identified as an active chemical component of both herb extracts. An effective dose of acteoside exhibited similar antiviral effects as each herb extract against RSV in vitro and in vivo. Collectively, these results suggest that extracts of Plantago asiatica and Clerodendrum trichotomum could provide a potent natural source of an antiviral drug candidate against RSV infection.